Antimycobacterial activity of selected medicinal plants extracts from Cameroon - Trigo, Gabriela (2014)
New drugs are highly needed to control mycobacterial infections. This study aimed at screening ethnobotanically selected plants extracted using organic solvents for their antimycobacterial activity. In vitro assays were performed on Mycobacterium smegmatis, Mycobacterium avium, Mycobacterium bovis Bacille Calmette Guerin (BCG), Mycobacterium tuberculosis and Mycobacterium ulcerans using the Resazurin Microtiter Assay. Cytotoxicity was assessed on Human lung fibroblast cells (MRC5) and bone marrow-derived macrophages (BMDM) using the MTS tetrazolium assay. The most promising extract from Annickia chlorantha stem bark (ACsbI) was tested for intracellular antimycobacterial activity against M. smegmatis using infected BMDM. Sixty crude extracts, 19 fractions, and 2 purified compounds were obtained from 19 Cameroonian medicinal plants. Results showed that crude extracts mainly inhibited BCG, while interface fractions from A. chlorantha stem bark (ACsbI) and stem (ACstI) displayed the strongest activity against M. ulcerans, with Minimal Inhibitory Concentrations (MIC) of 1.95 and 7.81 µg/ml respectively. Two compounds purified from Sorindeia juglandifolia fruits (SJfr 3.6 and SJfr 4.5) showed activity against BCG and M. ulcerans at 3.9 µg/ml and 62.5 µg/ml respectively. Finally, ACsbI showed no toxicity against MRC5 cells and BMDM and inhibited the growth of intracellular M. smegmatis. The results achieved in this investigation support the traditional to use of these plants and the need to investigate them in deeper details to be able to find alternatives for the existing antimycobacterial drugs.